1988
DOI: 10.2118/16659-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Slip/Stick Motion of the Bit

Abstract: This paper deals with torsional oscillations caused by slip/stick motion of the drill-collar section. This phenomenon is associated with a large-amplitude, saw-tooth-like variation in the applied torque. "Slip/stick motion" refers to the belief that the amplitude of the torsional oscillations becomes so large that the drill-collar section periodically comes to a complete stop and does not come free until enough torque is built up in the drillstring to overcome the static friction.A mathematical model of slip/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…It can be stated from Eqs. (14) and (15) that the value of S c;i generally increases with the natural angular frequency ω 0;i ¼ πi=L ffiffiffiffiffiffiffiffi ffi G=ρ p or the number of the mode shape i if the modal damping factor D i is equal for all mode shapes. The equation is independent of the length L of the torsional oscillator.…”
Section: Analytical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…It can be stated from Eqs. (14) and (15) that the value of S c;i generally increases with the natural angular frequency ω 0;i ¼ πi=L ffiffiffiffiffiffiffiffi ffi G=ρ p or the number of the mode shape i if the modal damping factor D i is equal for all mode shapes. The equation is independent of the length L of the torsional oscillator.…”
Section: Analytical Examplementioning
confidence: 99%
“…Several studies have focused on stick/slip of the whole drilling system, the most familiar kind of measured torsional vibration [11,14,15]. In this context, the drilling systems comprises the rig, a drillstring, and a bottomhole assembly (BHA) with measurement tools, and a bit to cut the formation.…”
Section: Introductionmentioning
confidence: 99%
“…Dawson et al 3 used a simple torsional pendulum to study stick-slip motion of the bit. Attempts to reveal the stick-slip phenomenon and its characteristics via torsional pendulum models were done by Kyllingstad and Halsey, 4 Lin and Wang, 5 Yigit and Christoforou, 6 and Richard et al 7,8 As reported in the literature, [9][10][11] the stick-slip performances and impact factors are investigated to search for controlling schemes of this vibration. In the meanwhile, measurement while drilling is used to optimize the drilling parameters to reduce stick slip.…”
Section: Introductionmentioning
confidence: 99%
“…Upon determining the critical speeds of drill strings, recommendations were set to execute drilling operations at speeds below the lowest critical speed to avoid resonance. This demonstration drives the need for a novel solution to attenuate the vibrations in the drill string, even while running close to critical speeds to maintain the optimum efficiency of drilling.Halsey et al [16] proposed a torque feedback control algorithm to minimize the stick-slip motion. The concept was to allow the rotary table speed to dampen the vibrations in the drill string by attenuating the reflections of the torsional waves.…”
mentioning
confidence: 99%
“…Halsey et al [16] proposed a torque feedback control algorithm to minimize the stick-slip motion. The concept was to allow the rotary table speed to dampen the vibrations in the drill string by attenuating the reflections of the torsional waves.…”
mentioning
confidence: 99%